Thin films sputter-deposited from EUROFER97 in argon and deuterium atmosphere: Material properties and deuterium retention. (March 2023) - Pitthan, E.; Petersson, P.; Tran, T.T.; Moldarev, D.; Kaur, R.; Shams-Latifi, J.; Ström, P.; Hans, M.; Rubel, M.; Primetzhofer, D.
Graphical abstract: Highlights: Plasma-facing components will be subjected to re-deposition in fusion reactors. Sputter-deposited films from EUROFER97 were obtained in Ar and D2 mix atmosphere. Ion beam analysis indicate very similar composition of the films and the bulk. Films feature different hardness, and microstructure in comparison to the bulk. Deposition in D2 + Ar atmosphere resulted in a low deuterium incorporation. Abstract: Sputter-deposited thin films (33–1160 nm) from EUROFER97 were obtained on different substrates (C, Si, W, MgO) in argon and a mix of argon and deuterium atmosphere. The composition, microstructure, and mechanical properties of the films were analyzed and compared to those of the bulk material. The films feature lower density (-10%), higher hardness (+79%), and smaller crystallites in comparison to the bulk. Despite such differences, the elemental atomic composition of the films and the bulk was very similar, as determined by ion beam analysis. Deposition in deuterium-containing atmosphere resulted in a low deuterium incorporation (0.28% of atomic content), indicating low retention of hydrogen-isotopes in the deposited material.